Peningkatan Kemampuan Membedakan Sampah Melalui Media Sampah Berbicara pada Penyandang Tunanetra - Irfan Putra; Ardisal Ardisal; Marlina Marlina (Jurnal Pendidikan Kebutuhan Khusus, 2018)
This research was motived by problems that found in the field, there were blind people who have problems in differentiating organic and anorganic waste. Based on the previous explanation, this objective of this research was to find out the effectivity of talking tool waste to improve the ability to distinguish organic and anorganic for blind people at the PSBN Tuah Sakato Padang. This type of this research by using quasi experiment with one group pretest-posttest design, the analyzed of the data using by Mann Whitney test. The sample consist of 5 blind people in the preparation class at PSBN Tuah Sakato Padang. The hypothesis of this research using t test, with significant level 5% (0,05).